Pilot study on discalculia using the "dyscalculia screener" of butterworth - María del Carmen Canto López; Inmaculada Menacho Jiménez; Esperanza Marchena Consejero; Manuel Aguilar Villagrán; Manuel A. García Sedeño (INFAD, 2015)
Having screening tools to identify students at risk of learning difficulties in mathematics is an essential resource to address future interventions that reduce failure and poor performance in mathematics.